Linking Environmental DNA and RNA for Improved Detection of the Marine Invasive Fanworm Sabella spallanzanii - von Ammon, Ulla; Wood, Susanna A.; Laroche, Olivier; Zaiko, Anastasija; Lavery, Shane D.; Inglis, Graeme J.; Pochon, Xavier (Frontiers in Marine Science, 2019)
Environmental DNA is increasingly being used in marine invasive species surveillance despite the inability to discriminate between contemporary intracellular (i.e. living) and extracellularly persistent (i.e. legacy) DNA fragments. Environmental RNA is emerging as a powerful alternative when distinguishing the living portion of a community is essential. A positive relationship between DNA and RNA signals may justify the use of DNA only for more rapid and cost-effective detections. In this study environmental DNA and RNA were co-extracted from settlement plates and water samples collected in the Auckland harbor, New Zealand. Samples were analyzed using a Sabella spallanzanii specific droplet digital PCR assay combined with metabarcoding of metazoan communities (Cytochrome c oxidase subunit I). The number and magnitude of S. spallanzanii detections was higher in DNA compared to RNA, and in water samples. A Receiver Operator Characteristics analysis supported a relationship between the magnitude of DNA signal and the likelihood of RNA detection for both sampled matrices. A prediction threshold of 400 COI copies in DNA samples provides an indicator for inferring the presence of living S. spallanzanii population in the conditions tested in this study. Metabarcoding community analysis revealed the taxonomic composition of the water samples to be more diverse than the plate samples which were largely dominated by mollusks. There was a strong association between mollusks and putative extracellular droplet digital PCR signals. Nevertheless, droplet digital PCR detection signals based on environmental DNA were negatively correlated with metabarcoding diversity indices on plates. This highlights complex interactions between environmental DNA and RNA detections and environmental matrices that can affect targeted approaches and need to be considered when designing surveillance programmes.